Motivational Interviewing in Patients with Chronic Conditions - Alfarisi, Naufal Raihan; Lestari, Dwi; Sujianto, Untung (Indonesian Journal of Global Health Research, 2025)
Nurse service in the world today requires supporting therapy to overcome complex problems including biologically, psychologically, socially, culturally and spiritually. In chronic patients there are many supporting implementation, one of which is motivational interviewing which explains motivational communication as a tool in minimizing the effects of problems that occur in chronic patients. Motivational interviewing can help more patient awareness and compliance leads to more careful responsibilities on treatment and health. Objectives: To determine the effect of motivational interviewing on chronic patients. Literature search using Data Based Sciencedirect, Scopus, Proquest, JStor, and Pubmed. The keywords used are "Interventions" and "Motivational Interviewing" and "Nursing" and "Effective" and "Chronic Diseases". Method: The method used to compile information in this article is by using scoping review, with a span of 2019-2024, screening of articles is guided by the prism. Pubmed (133 articles), Scopus (3 articles), Sciencedirect (125 articles) and proquest (30 articles) from the results of the analysis of articles that can be taken according to criteria are 7. obtained 3 themes, the influence of clinical conditions, on secondary outcomes and health services. Motivational interviewing in chronic patients has a positive impact on patients and health services. So it is hoped that this research will be a reference for patient services with chronic conditions.